2013
DOI: 10.1016/j.mayocp.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Cutting: An Evidence-Based Approach to Clinical Management for the Primary Care Physician

Abstract: The United States has more than 1.5 million immigrants from countries in Africa and the Middle East where female genital cutting (FGC) is known to occur. Often, FGC occurs in infancy and childhood in the countries where it is practiced, but patients of any age can present with complications. Lack of understanding of this common problem can potentially alienate and lower quality of care for this patient population. We provide an introduction to the practice of FGC and practice guidelines for the primary care ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…This statement is supported by the findings of several studies (UN, Klouman; Msuya; Snow, as cited in Ref. [11]). Hearst and Molnar [10] found that the mother's education has a crucial influence on whether they will allow FGM to be performed on their daughters.…”
Section: Individual Levelsupporting
confidence: 67%
See 4 more Smart Citations
“…This statement is supported by the findings of several studies (UN, Klouman; Msuya; Snow, as cited in Ref. [11]). Hearst and Molnar [10] found that the mother's education has a crucial influence on whether they will allow FGM to be performed on their daughters.…”
Section: Individual Levelsupporting
confidence: 67%
“…This was also emphasised by UNICEF report, Kandala and Rahlenbeck's (as cited in Ref. [11]) findings, that showed that the higher the educational level of the mother, the lower the likelihood for them to let their daughters undergo FGM and show support for the perpetuation of the practice. Afifi et al (as cited in Ref.…”
Section: Individual Levelmentioning
confidence: 88%
See 3 more Smart Citations